Flin Flon: A Study of Company-Community Relations in a Single Enterprise Community - Robson, Robert (Urban History Review / Revue d'histoire urbaine, 1984)
Defined as a single enterprise community, Flin Flon's development was largely dictated by the policy of the Hudson Bay Mining and Smelting Company Ltd. In its formative stage, the H.B.M.&S. assumed responsibility for both industrial and community expansion, but as the opportunity arose, the Company divested itself of community oriented projects. By 1946, when Flin Flon was granted town status, the Company has largely removed itself from direct involvement in community affairs. This evolving tendency on the part of the H.B.M.&S. to separate industrial and community interest corresponded to the fulfillment of labour needs. Essentially, Company participation in community development was directly related to labour supply, so much so, that when H.B.M.&.S finally perceived a guaranteed labour force, it withdrew from community affairs.